Intertextuality in 2024 Indonesian Presidential Debate Memes on X - Valkenburg, Odytyas Fanni Anggraheni Dewanti; Chitra, Bima Prana; Erwina, Emmy (TRANSFORM: Journal of English Language Teaching and Learning, 2025)
The advent of social media has led to changes in the way people communicate. One such change is in the usage of memes, especially among the younger generation. With Gen Z and Millennials making up over 50% of the voters in the 2024 Indonesian presidential election, memes became one way they voiced their opinions on the televised debates held prior to the election. This research aimed to find out how intertextuality impacted the meaning of political memes about the 2024 Indonesian presidential candidate debates. This research employed the qualitative method. The critical discourse analysis by Fairclough was used to analyze the data. The memes were limited only to those that referenced works of literature that were uploaded on the social media platform X on the day of or the day after the first, third, and fifth presidential debates. The findings indicated that intertextuality in memes added a layer of complexity and nuance that allowed the creators to criticize the candidates implicitly through humor, thus circumventing censorship and IET laws. The memes functioned as a mode of political advocacy and public discussion, mainly in the form of criticism of the candidates’ actions during the debates. Criticism of the first and third debates likely contributed to the calmer proceedings of the final debate.